Ð˜ÑÑÐ»ÐµÐ´Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð²Ð»Ð¸ÑÐ½Ð¸Ñ ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð² Ð½Ð° Ð»Ð¸Ð¿Ð¾ÑÐ¾Ð¼Ñ‹ Ð¸Ð· ÑÑƒÐ¼Ð¼Ð°Ñ€Ð½Ñ‹Ñ… Ð»Ð¸Ð¿Ð¸Ð´Ð¾Ð² ÑÐ¿ÐµÑ€Ð¼Ð°Ñ‚Ð¾Ð·Ð¾Ð¸Ð´Ð¾Ð² ÑÐ¾Ð±Ð°ÐºÐ¸ - Linnik, T. P.; Dyubko, T. S.; Yegorov, M. I.; Pivovarenko, V. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
The mechanism of interaction between the cryoprotective agents (CPAs): ethylene glycol (EG), glycerol and N,N-dimethylformamide (DMFA) with lipid bilayer of liposomes formed from total lipids of canine spermatozoa by fluorescent spectroscopy using new fluorescent probe of flavonoid origin: 3-hydroxy-4â€™-(N,N-dimethylamine)flavon (FME). It has been established that among the studied CPAs (glycerol, EG, DMFA) the highest effect on the form of FME fluorescence spectrum associated to lipid bilayer is rendered by DMFA. The effect rate of the studies CPAs on liposomes is determined by hydrophobic-hydrophilic balance of their molecules. DMFA predominantly affects lipid bilayer by hydrophobic interaction, and glycerol and EG mainly influence hydrate layer of polar â€œheadsâ€ of phospholipids by forming intermolecular hydrogen bonds.